Analisis Efektivitas Transformasi Digitalisasi Pelayanan Kesehatan di RSAD Brawijaya Surabaya - Dwi Darmanto; Agusta Dian Elina; Dyna Sri Mulawardhani (Jurnal Pengabdian Ilmu Kesehatan, 2025)
The digital transformation in this study focused on three digital transformation programs implemented at Brawijaya Army Hospital: online registration services via Mobile JKN, electronic medical records, and free medication delivery services for patients. The results of this study indicate limitations in facilities and infrastructure, human resources, technological infrastructure in digital transformation, and a lack of outreach to patients regarding the digital transformation program at Brawijaya Army Hospital. Therefore, the researcher proposes several solutions to the problems that arise in the digital transformation of healthcare services at Brawijaya Army Hospital. Possible solutions include increasing the budget for improving facilities, infrastructure, and providing an independent counter for online registration via Mobile JKN. Furthermore, innovation is needed, namely creating a website or mobile application that can provide information about electronic medical records that can be accessed by patients independently with guaranteed security regarding patient personal data. Finally, a possible solution is to increase human resources with IT skills and capabilities to overcome problems with medical record servers when they are down or under maintenance and to create a website or mobile application for medical records that can be accessed by patients.